Evidence for the decay B+c -> J/[psi]3π+2π- - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Journal of high energy physics, 2014)
Evidence is presented for the decay $ B_{c}^{+}→ {J \left/ {{\uppsi\;3{\uppi^{+}}2{\uppi^{-}}}} \right.} $using proton-proton collision data, corresponding to an integrated luminosity of 3 fb−1, collected with the LHCb detector. A signal yield of 32 ± 8 decays is found with a significance of 4.5 standard deviations. The ratio of the branching fraction of the $ B_{c}^{+}→ {J \left/ {{\uppsi\;3{\uppi^{+}}2{\uppi^{-}}}} \right.} $decay to that of the $ B_{c}^{+}→ {J \left/ {{\uppsi\;{\uppi^{+}}}} \right.} $decay is measured to be$ \frac{{\mathcal{B}\left( {B_{c}^{+}→ {J \left/ {{\uppsi\;3{\uppi^{+}}2{\uppi^{-}}}} \right.}} \right)}}{{\mathcal{B}\left( {B_{c}^{+}→ {J \left/ {{\uppsi\;{\uppi^{+}}}} \right.}} \right)}}=1.74± 0.44± 0.24, $where the first uncertainty is statistical and the second is systematic.